Prostitution - Lankford, Ronald D. (Social issues firsthand, 2008)
I was a teenage prostitute / Lisa Carver -- I am a prostitute and a writer / Anonymous -- Interview with a male sex worker / Cindy-Lou Dale -- Confessions of an ivy league call girl / Jeannette Angell -- Leaving prostitution behind / clandestine call girl -- The unionization of sex workers : interview with Ana Lopez from the International Union of Sex Workers -- Sex with prostitutes is exciting and honest / Sebastian Horsley -- The uneasy relationship between prostitutes and feminists / Teri Goodson -- A courtesan's spiritual calling / Amanda Brooks -- Sex workers are feminists : feminism and sex work -- Memoirs of a Hollywood prostitute / Daniel Maurer -- A downward spiral / Frederique Delacoste and Priscilla Alexander, editors -- Living as an HIV-positive porn star and escort / Tony Valenzuela -- A former prostitute finds God / Shelly Lubben -- Rescuing girls from prostitution / Somaly Mam